Synthesis, anti-mycobacterial activity and DNA sequence-selectivity of a library of biaryl-motifs containing polyamides. Issue 13 (1st July 2015) - Brucoli, Federico; Guzman, Juan D.; Maitra, Arundhati; James, Colin H.; Fox, Keith R.; Bhakta, Sanjib
Graphical abstract: Abstract: The alarming rise of extensively drug-resistant tuberculosis (XDR-TB) strains, compel the development of new molecules with novel modes of action to control this world health emergency. Distamycin analogues containing N-terminal biaryl-motifs2 ( 1 - 5 )( 1 - 7 ) were synthesised using a solution-phase approach and evaluated for their anti-mycobacterial activity and DNA-sequence selectivity. Thiophene dimer motif-containing polyamide2 ( 2, 6 ) exhibited 10-fold higher inhibitory activity against Mycobacterium tuberculosis compared to distamycin and library member2 ( 5, 7 ) showed high binding affinity for the 5′-ACATAT-3′ sequence.